CRISPR-Hybrid: A CRISPR-Mediated Intracellular Directed Evolution Platform for RNA Aptamers - Qiwen Su-Tobon; Jiayi Fan; Michael Goldstein; Kevin Feeney; Hongyuan Ren; Patrick Autissier; Peiyi Wang; Yingzi Huang; Udayan Mohanty; Jia Niu (Nature Communications)
Abstract Recent advances in gene editing and precise regulation of gene expression based on CRISPR technologies have provided powerful tools for the understanding and manipulation of gene functions. Fusing RNA aptamers to the sgRNA of CRISPR can recruit cognate RNA-binding protein (RBP) effectors to target genomic sites, and the expression of sgRNA containing different RNA aptamers permit simultaneous multiplexed and multifunctional gene regulations. Here, we report an intracellular directed evolution platform for RNA aptamers against intracellularly expressed RBPs. We optimize a bacterial CRISPR-hybrid system coupled with FACS, and identified high affinity RNA aptamers orthogonal to existing aptamer-RBP pairs. Application of orthogonal aptamer-RBP pairs in multiplexed CRISPR allows effective simultaneous transcriptional activation and repression of endogenous genes in mammalian cells.